Analysis and Measurement of the Impact of Global Supply Chain Strategies on Economic Reform Programs and Poverty in IRAQ - Maiami Salal Sahib Al-shukri (International Journal of Supply Chain Management, 2020)
Abstract- Over the last three decades, global supply chains (GSCs) have increasingly gained importance in linking developing countries to international markets. This investigation intends to take a gander at the present status of poverty and existing reform approaches in Iraq. This is a continuous research for the policy estimations in Iraq, which exhibited the poverty circumstance after the economic reforms. This study utilized a time period of post war era from 2005 to 2017 to examine the poverty situation in Iraq after the reform agenda. The study suggests that poverty should genuinely take into consideration the institutional, social and political elements. In GSCs, competitiveness (and thus delocalization choices) is determined by a wide range of factors, especially by the quality of policies influencing the overall  business  environment. Economic reforms do not fairly distribute income and employment which is imperative for the decrease in the poverty. With the expanding globalization of the world economy, it is recommended that nations seeking after fare approaches dependent on specific advantages will achieve faster growth. Solid financial development will give enough assets to improve the status of poor people. However, government should take necessary action in GSC specifically poverty alleviation driven.  Otherwise the poverty may remain a big problem for Iraq even after achieving economic reforms and growth.